Three-Leaf-Clover Thyroid and Minimally Invasive Trans-Cervical Synchronous Thyroidectomy and Ectopic Mediastinal Thyroid Tissue Removal: Does the Age of the Patient Count amid a Multifaceted Strategy? - Claudiu Nistor; Mihai-Lucian Ciobica; Oana-Claudia Sima; Anca-Pati Cucu; Mihai Costachescu; Adrian Ciuche; Lucian-George Eftimie; Dana Terzea; Mara Carsote (Clinics and Practice)
Background: Ectopic organ-associated conditions belong to the larger panel of developmental ailments, and among this challenging medical and surgical chapter, ectopic endocrine glands-related picture is mostly focused on the presence of the ectopic parathyroid and thyroid. Ectopic thyroid tissue within mediastinum (ETTM) stands for a less common ETT site; while, globally, less than 1% of the mediastinum masses are ETTM. Objective: We aim to introduce a rare case of ETTM in a senior lady to whom one-time synchronous thyroidectomy with ETT removal was successfully performed via a minimally invasive modern procedure upon cervicotomy and intra-operatory use of the Cooper thymectomy retractor. Results: The panel of pros and cons with respect to providing endocrine thoracic surgery for ETTM resection in a 73-year-old subject is discussed amid a PubMed search of original English-language original reports from January 2000 until 15 August 2024 in order to identify similar distinct cases (individuals of 70 years or older who underwent surgery for ETTM). Conclusions: 1. We propose the term “three-leaf-clover thyroid” to capture the imaging essence of having an enlargement of both (eutopic) thyroid lobes and ETTM. 2. The modern surgical approach under these circumstances provided a rapid patient recovery with a low rate of complications and a minimum hospital stay. Hence, the procedure may be expanded to older patients after a careful consideration of their co-morbidities and of the need to releasing connected complaints (e.g., a 7-month history of intermittent dyspneea was found in this case with post-operatory remission). 3. The management remains a matter of individualised decision, and age may not be a limiting factor. 4. At the present time, this case adds to the very limited number of similar published cases in the mentioned age group that we could identify (seven patients, aged between 72 and 84; male-to-female ratio of 5 to 2; the rate of malignant ETTM was 3/7); of these cases, not all were reported to have a trans-cervical approach, and none reported the use of the Cooper thymectomy retractor to help the overall surgical procedure. This innovative surgical procedure offers the advantage of avoiding a sternotomy incision which has clear functional and aesthetic implications, while the video-assisted approach allows optimal visualization of the mediastinal anatomy and safe vascular sealing under visual control, without the risk of a major hemorrhage.